Effect of Feeding Nettle Plants to Mice - AL-KHAZRJI, A. K.; BAYOUMI, M. A. (The Libyan Journal of Agriculture, 2023)
An experiment was conducted to study the possibility of utilizing the nettle plant (Urtica urens) as a feed for farm animals in Libya. Green and powdered leaves of nettle plants were mixed with a standard chick diet and fed to albino mice. Mice fed chopped green nettle leaves exhibited either reddening and/or blistering skin around the mouth. The irritational effect was eliminated when the leaves of the plant were either sun or oven dried.